2006
DOI: 10.1111/j.1471-6402.2006.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Objectification Theory with Lesbian Women

Abstract: This study extends research on objectification theory as it applies to eating disorder symptomatology by examining whether its tenets generalize to women identifying as lesbian. Lesbian women (N= 181) and a comparison sample of heterosexual women (N= 196) completed measures of objectification theory constructs (interpersonal sexual objectification, body surveillance, body shame, interoceptive awareness, disordered eating). The model of objectification theory was tested separately for lesbian and heterosexual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
166
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(192 citation statements)
references
References 37 publications
(86 reference statements)
19
166
3
4
Order By: Relevance
“…Empirical studies have demonstrated that both interpersonal forms (Hill & Fischer, 2008;Kozee & Tylka, 2006;Kozee, Tylka, Augustus-Horvath, & Denchik, 2007; BODY GUILT Moradi, Dirks, & Matteson, 2005) and media forms (Harper & Tiggemann, 2008;Morry & Staska, 2001) of sexual objectification predict state self-objectification and self-surveillance.…”
Section: Self-objectification and Related Consequencesmentioning
confidence: 99%
“…Empirical studies have demonstrated that both interpersonal forms (Hill & Fischer, 2008;Kozee & Tylka, 2006;Kozee, Tylka, Augustus-Horvath, & Denchik, 2007; BODY GUILT Moradi, Dirks, & Matteson, 2005) and media forms (Harper & Tiggemann, 2008;Morry & Staska, 2001) of sexual objectification predict state self-objectification and self-surveillance.…”
Section: Self-objectification and Related Consequencesmentioning
confidence: 99%
“…Empirical studies have demonstrated that both interpersonal forms (Hill & Fischer, 2007;Kozee & Tylka, 2006; Running head: OBJECTIFICATION THEORY AND COSMETIC SURGERY 5 Kozee, Tylka, Augustus-Horvath, & Denchik, 2007;Moradi, Dirks, & Matteson, 2005) and media forms (Harper & Tiggemann, 2008;Morry & Staska, 2001) of sexual objectification contribute to self-objectification. Moreover, there is strong evidence from studies of women across North America, Australia, and the U.K. indicating that self-objectification, and the concomitant self-surveillance, exact significant costs on womenÕs subjective well-being (Breines, Crocker, & Garcia, 2008;Fairchild & Rudman, 2008) and cognitive performance (Fredrickson, Roberts, Noll, Quinn, & Twenge, 1998;Quinn, Kallen, Twenge, & Fredrickson, 2006), with a greater prevalence of self-harming behavior (Harell, Fredrickson, Pomerleau, Nolen-Hoeksema, 2006;Muehlenkamp, Swanson, & Brausch, 2005) and a disproportionately higher rate of mental health risks, including depression (Grabe, Hyde, & Lindberg, 2007;Tiggemann & Kuring, 2004), disordered eating (Calogero, Davis, & Thompson, 2005;Tylka & Hill, 2004), and sexual dysfunction (Calogero & Thompson, 2009b;Steer & Tiggemann, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Gaze, which is a direct form of interpersonal sexual objectification (Fredrickson and Roberts 1997), may impact women's and men's body image and eating behaviors differently based on their sexual orientation, and this difference may be more pronounced for men. Girls, regardless of their sexual orientation, tend to start receiving messages to be attractive well before their sexual identity is in place, which may or may not influence their body image as they mature (Kozee and Tylka 2006). Gay men also experience male gaze (Wood 2004) and often feel pressure to achieve the mesomorphic body ideal because they wish to attract men who also fit this ideal (Carper et al 2010;Wiseman and Moradi 2010).…”
Section: Stream One: Gendered Body Constructionsmentioning
confidence: 99%
“…Professionals also could help girls and women develop an appreciative view of their body and its ability to function, as this appreciation may protect women from the potentially negative consequences of self-objectification (Rubin and Steinberg 2011;Wood-Barcalow et al 2010;Kozee and Tylka 2006). As Rubin and Steinberg found, pregnancy, a manifestation of the body's functionality, is one opportune period for this intervention.…”
Section: Challenge Myths Of the Gendered Body Idealmentioning
confidence: 99%